Antimicrobial susceptibility of ileal symbiont intracellularis isolated from pigs with proliferative enteropathy. - McOrist, S (1995)
Proliferative enteropathy is caused by the microaerophilic obligate intracellular bacterium ileal symbiont (IS) intracellularis. Treatment of this disease is problematic because of the lack of in vivo or in vitro data on the activities of antimicrobial agents. A new procedure for determining the susceptibility of IS intracellularis was developed by using a tissue culture system which promotes the in vitro multiplication of this organism. Nineteen antimicrobial agents were evaluated in triplicate cultures for their intracellular and extracellular activities against up to three IS intracellularis strains isolated from pigs with proliferative enteropathy. The MIC was defined as the lowest concentration which prevented multiplication of 99% of the IS intracellularis isolates. Penicillin, erythromycin, difloxacin, virginiamycin, and chlortetracycline were the most active compounds tested, all with MICs of < or = 1 microgram/ml. Tiamulin and tilmicosin were the next most active compounds, with MICs of < or = 4 micrograms/ml. The MICs of aminoglycosides were generally > 32 micrograms/ml. Both lincomycin and tylosin were relatively inactive against the IS intracellularis strains tested, with MICs of 32 and 64 micrograms/ml, respectively. These results indicate that some compounds capable of intracytoplasmic accumulation and blocking bacterial protein synthesis were active against IS intracellularis strains isolated from pigs with proliferative enteropathy. The in vitro cultivation system shows promise as a method for studying the interaction between IS intracellularis and antimicrobial agents and for screening new antibiotics for use in therapy.